Inovasi IoT (Internet Of Things) Sebagai Sistem Monitoring Kualitas Air Dan Peringatan Dini Banjir - Utoyo Efendi; Muhlasin Muhlasin; Machrus Ali (Universitas Darul Ulum, 2025)
The Internet of Things (IoT) is a concept where various physical devices can connect to the internet and communicate with each other to collect, share, and analyze data.. This technology has developed rapidly and been applied in various fields, including water quality monitoring and flood early warning systems. This research aims to study building innovations as a water quality monitoring and flood early warning system based on the Internet of Things (IoT). Sensors as measuring physical or environmental parameters, such as temperature, humidity, pH, and water level, Actuators are devices that perform actions based on received data, and networks serve as the infrastructure connecting IoT devices for data communication, such as MQTT or CoAP And platforms as systems that manage and analyze data collected from various sensors. These IoT components are expected to monitor water quality parameters, integrate data and provide early warnings in case of significant changes in water quality or potential flooding